Landscaping the structures of GAVI country vaccine supply chains and testing the effects of radical redesign. Issue 36 (26th August 2015) - Lee, Bruce Y.; Connor, Diana L.; Wateska, Angela R.; Norman, Bryan A.; Rajgopal, Jayant; Cakouros, Brigid E.; Chen, Sheng-I.; Claypool, Erin G.; Haidari, Leila A.; Karir, Veena; Leonard, Jim; Mueller, Leslie E.; et al.
Highlights Many GAVI-eligible countries' vaccine supply chains were designed in the 1970s. Supply chain design does not correlate closely with country characteristics. We used HERMES to model current and radically simpler designs in sample countries. Simpler designs reduce operating costs and warrant consideration in many countries.